2012
DOI: 10.1002/art.33383
|View full text |Cite
|
Sign up to set email alerts
|

Phase IIb dose‐ranging study of the oral JAK inhibitor tofacitinib (CP‐690,550) or adalimumab monotherapy versus placebo in patients with active rheumatoid arthritis with an inadequate response to disease‐modifying antirheumatic drugs

Abstract: Objective. To compare the efficacy, safety, and tolerability of 5 doses of oral tofacitinib (CP-690,550) or adalimumab monotherapy with placebo for the treatment of active rheumatoid arthritis (RA) in patients with an inadequate response to disease-modifying antirheumatic drugs.Methods. In this 24-week, double-blind, phase IIb study, patients with RA (n ‫؍‬ 384) were randomized to receive placebo, tofacitinib at 1, 3, 5, 10, or 15 mg administered orally twice a day, or adalimumab at 40 mg injected subcutaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
286
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 350 publications
(317 citation statements)
references
References 34 publications
(26 reference statements)
16
286
0
11
Order By: Relevance
“…The secondary efficacy end points analyzed at all time points included the following: the ACR20, ACR50, and ACR70 response rates and the proportions of patients achieving disease remission according to the 3-variable Disease Activity Score in 28 joints (DAS28) using the CRP (DAS28-CRP) (11), a DAS28-CRP of Ͻ2.6, and change in components of the ACR core set of disease activity measures (12), including the Health Assessment Questionnaire disability index (HAQ DI) (13), the Short Form 36 (SF-36) Health Survey (physical component summary [PCS] score and mental component summary [MCS] score) (14), and the Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) subscale (15). Efficacy assessments were carried out at baseline and at weeks 2,4,6,8,12,16,20, and 24 or at the time of early termination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The secondary efficacy end points analyzed at all time points included the following: the ACR20, ACR50, and ACR70 response rates and the proportions of patients achieving disease remission according to the 3-variable Disease Activity Score in 28 joints (DAS28) using the CRP (DAS28-CRP) (11), a DAS28-CRP of Ͻ2.6, and change in components of the ACR core set of disease activity measures (12), including the Health Assessment Questionnaire disability index (HAQ DI) (13), the Short Form 36 (SF-36) Health Survey (physical component summary [PCS] score and mental component summary [MCS] score) (14), and the Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) subscale (15). Efficacy assessments were carried out at baseline and at weeks 2,4,6,8,12,16,20, and 24 or at the time of early termination.…”
Section: Methodsmentioning
confidence: 99%
“…To more fully characterize the efficacy and safety dose-response profile of tofacitinib over a longer period of time, two phase IIb trials of 24 weeks duration were initiated: one to assess tofacitinib as monotherapy (8), and the other (reported here) to assess tofacitinib as an addition to stable background MTX treatment. The primary objective of the current study was to compare the efficacy of 6 dosages of tofacitinib (1 mg twice daily, 3 mg twice daily, 5 mg twice daily, 10 mg twice daily, and 15 mg twice daily, and 20 mg/day) versus placebo, over 12 weeks, for the treatment of signs and symptoms of RA in patients with active RA receiving a stable dosage of MTX who had an inadequate response to MTX alone.…”
mentioning
confidence: 99%
“…Safety of tofacitinib was evaluated in six phase 3 clinical trials [11][12][13][14][15][16] , four phase 2 trials [6][7][8][9] , two phase 1 trials [17][18] , and a study evaluating the impact on latent tuberculosis infection (LTBI) in a mouse model due to concerns with a risk of reactivation with treatments (i.e., tumor necrosis factor alpha inhibitors) for chronic inflammatory disorders, including rheumatoid arthritis [19] . Several of the phase 2 and 3 trials have been reported in two meta-analyses to evaluate efficacy and safety of tofacitinib for treatment of rheumatoid arthritis [20][21] .…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…Tofacitinib has demonstrated significant ACR20 response in phase 2 trials as monotherapy and with background therapy with methotrexate [6][7][8][9][10] . Six phase 3 trials have been conducted to evaluate the efficacy of tofacitinib under the oral rheumatoid arthritis triaLs (ORAL) series.…”
Section: Efficacy Studiesmentioning
confidence: 99%
“…[2][3][4] For example, tofacitinib (CP-690,550), which inhibits the Jak1, Jak2, and Jak3 isoforms, is concluding phase 3 trials for rheumatoid arthritis. [5][6][7][8][9] Obtaining selective JAK inhibitors has been a challenge. Because Jak2 mediates erythropoietin (EPO) signaling, 10,11 its inhibition may lead to anemia.…”
Section: Introductionmentioning
confidence: 99%